National Identity under Economic Integration - Chun-Fang Chiang; Jin-Tan Liu; Tsai-Wei Wen (Global Labor Organization (GLO), 2018)
This study empirically investigates how economic integration influences individuals' national identity. Due to historical reasons and unique cross-strait politics, some people in Taiwan identify themselves as Chinese while others identify themselves as Taiwanese. Using individual survey data with the outward investment data at the industry level from 1992 to 2009, we find that the rising investment in China has strengthened Taiwanese identity and has reduced the probability of voting for the Pan-Blue parties. The effects are much stronger for unskilled workers than for skilled workers, suggesting that outward investment in China may not only have economic impact on the economy but may also deepen the political polarization in Taiwan.
Keywords: F50; Z10; D72; 330; identity; economic integration; voting behavior